Propuesta de plan de marketing estratégico para la empresa EcoSolaris S.A.S (2023)
This monograph refers to the initiative of the company EcoSolaris SAS whoseeks to provide alternative energies through panels that allow lighting to be brought to homes and businesses, in addition to the supply of solar equipment and LED light ting in such a way that it generates reliability and economy with products of excellent quality, tending to wards ecological alternativesthat reduce the economic benefits of the use of renewable energies and give a greater use of the systems forendusers.